Creating instructional materials - Bullough, Robert V. (Columbus : Merrill Publishing Company, 1978)
The Importance of visual teaching materials has been recognized for centuries, but only in recent years have the vast implications for the use of such materials been fully appreciated. Still pictures were formerly the most common kind of media used in the classroom.
1. A Basis for the design and selection of media -- 2. Picture preservation -- 3. Illustration -- 4. Lettering techniques -- 5. Visual design -- 6. Poster, charts, and graphs -- 7. Copying and duplicating processes -- 8. Overhead transparencies -- 9. Display and demonstration boards -- 10. three-dimensional teaching devices -- 11. photography -- 12. Audio techniques -- 13. Television.
Includes bibliographical references and index.
Keywords: AUDIO VISUAL MATERIALS